Human African trypanosomiasis cases diagnosed in non-endemic countries (2011-2020). - Jose R Franco; Giuliano Cecchi; Gerardo Priotto; Massimo Paone; Augustin Kadima Ebeja; Pere P Simarro; Abdoulaye Diarra; Dieudonné Sankara; Weining Zhao; Daniel Argaw Dagne (PLoS Neglected Tropical Diseases)
Background Sleeping sickness, or human African trypanosomiasis (HAT), is transmitted by tsetse flies in endemic foci in sub-Saharan Africa. Because of international travel and population movements, cases are also occasionally diagnosed in non-endemic countries. Methodology/principal findings Antitrypanosomal medicines to treat the disease are available gratis through the World Health Organization (WHO) thanks to a public-private partnership, and exclusive distribution of the majority of them enables WHO to gather information on all exported cases. Data collected by WHO are complemented by case reports and scientific publications. During 2011-2020, 49 cases of HAT were diagnosed in 16 non-endemic countries across five continents: 35 cases were caused by Trypanosoma brucei rhodesiense, mainly in tourists visiting wildlife areas in eastern and southern Africa, and 14 cases were due to T. b. gambiense, mainly in African migrants originating from or visiting endemic areas in western and central Africa. Conclusions/significance HAT diagnosis in non-endemic countries is rare and can be challenging, but alertness and surveillance must be maintained to contribute to WHO's elimination goals. Early detection is particularly important as it considerably improves the prognosis.